2015
DOI: 10.1016/j.jsams.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The association between resistance exercise and cardiovascular disease risk in women

Abstract: Objectives The objective of this study was to examine the association between resistance exercise and cardiovascular disease (CVD) risk, independent of body composition, physical activity and aerobic capacity, in healthy women. Design A cross-sectional analysis including 7321 women with no history of heart disease, hypertension or diabetes was performed. Methods Participation in resistance exercise was self-reported and body weight and height was measured. A single CVD risk score was established via factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…(7) Additionally, studies examining measured muscle strength and cardiovascular disease have shown that grip strength is associated with fewer cardiovascular risk factors as well as a lower risk of cardiovascular events. (13, 22)…”
Section: Discussionmentioning
confidence: 99%
“…(7) Additionally, studies examining measured muscle strength and cardiovascular disease have shown that grip strength is associated with fewer cardiovascular risk factors as well as a lower risk of cardiovascular events. (13, 22)…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical exercise is associated with numerous health benefits to reduce the progression and development of obesity, T2D, and CVD (914). Several randomized clinical trials have demonstrated that lifestyle interventions including moderate exercise and a healthy diet improve cardiovascular health in at-risk populations (72, 73). Individuals with metabolic syndrome who participated in a 4 month program of either a diet (caloric restriction) or exercise intervention had reduced adiposity, decreased systolic, diastolic and mean arterial blood pressure, and lower total and low-density lipoprotein (LDL) cholesterol lipid profiles compared to the control group (12).…”
Section: Exercise Training Improves Cardiovascular Healthmentioning
confidence: 99%
“…Evidence has accumulated that suggests that engaging in some form of muscle strengthening activity, such as RT, has an impact on a range of health and morbidity related risk factors [4145], multi-morbidity risk [46, 47], and all-cause mortality [4850], across both healthy and clinical populations. However, a question remains as to how important a place RT should have in current physical activity and exercise guidelines for public health.…”
Section: Resistance Training For Public Healthmentioning
confidence: 99%